RANCANG BANGUN MESIN PEMISAH BERONDOL SAWIT - Hasan, Muhammad; Yulianto, Ferisa; Anggraini, Asty; Erwansyah; Somawardi (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Endmill cutting edges are one of the many cutting tools found in machining processes. Apart from that, endmill are blades made of highspeed metal (HSS), cobalt and tungsten carbide. Endmills often function as a medium for making holes, profiling, contouring, slotting, counterboring, drilling, reaming and faching. In endmill sharpening, we often still sharpen manually. One of which is found in the lotus and bongman workshops. The drawback that results from this manual sharpening system is that it is limited by time. Uniformity of cutting angles, and physical injuries experienced by the endmill and the operator who carries it out. With this, we got the results of the design of an endmill cutting machine with a drive system using an electric motor with a specification of 0.5hp with an rpm of 2760. For the corner sharpening system using a shaft sleeve connected to a drill chuck and using a groove direction indicator, the movement of the division is shown in a sliding movement with 1 line calculated as 1mm offeed. On the findings on the design of an endmill cutting edge sharpening machine.